Water-flow stress differentially affects the morphological, anatomical, and mechanical traits of Osmunda x intermedia (Osmundaceae) populations growing inside and outside the river curve - Hara, Shunsuke; Shiba, Masayuki; Fukuda, Tatsuya (Frontiers in Plant Science, 2025)
The curve of a river bed creates a difference in the speed of water flow inside and outside this curve, indicating that plants growing along the river experience differential water-flow stresses during sudden floods caused by heavy rains. In this study, we conducted morphological, anatomical, and mechanical analyses using Osmunda x intermedia (Honda) Sugim. (Osmundaceae), a hybrid of Osmunda japonica Thunb. and the rheophytic O. lancea Thunb., growing inside and outside the river curve to elucidate the plant traits influenced by differential water-flow stresses. The external morphological analysis revealed that the O. x intermedia populations growing both inside and outside the river curve exhibited values intermediate between those of the parent species. However, the results of the anatomical and mechanical analyses of the petioles of the hybrid species did not necessarily reveal values intermediate between those of the parent species; however, in the hybrid species, the cell wall volume per unit volume was related to petiole strength, and the cell wall volume per unit volume of the hybrid population growing inside the river curve was significantly higher than that in the parent species or the hybrid population outside the river curve. In addition, the flexibility of petioles in the hybrid population growing outside the curve was associated with a lower cell wall density in the sterome than in that inside the curve, which may cause elastic bending that bends the cells further because of thinner cell walls. The results obtained in our study revealed that O. x intermedia adapts to different water-flow stresses through complex anatomical and mechanical changes that cannot be determined from external morphology alone.